2020
DOI: 10.3390/ijerph17144934
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ideological Variables in the Denial of Violence Against Women: The Role of Sexism and Social Dominance Orientation in the Spanish Context

Abstract: Violence against women in heterosexual intimate relationships is a major social problem with serious physical and psychological consequences for the victims. There is a line of research that seeks to analyze how ideological variables and contextual variables influence the way in which this type of violence is perceived. This study analyzed the relationship between hostile sexism, benevolent sexism and social dominance in the acceptance of the myths about violence against women in intimate relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 44 publications
1
9
0
4
Order By: Relevance
“…Right-wing authoritarianism is expressed by, among other things, a commitment to traditional values and a conservative view of gender roles. Thus, there is an assumption that individuals who exhibit high levels of right-wing authoritarianism tend to stereotype perceptions of rape and assign blame to the victim (Canto et al, 2020 , 2021 ). By simply belonging to non-binary group, its members stand in opposition to the values of right-wing authoritarianism - respect for traditional social values, and entrenched thinking about gender binarity and assigned social roles for men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Right-wing authoritarianism is expressed by, among other things, a commitment to traditional values and a conservative view of gender roles. Thus, there is an assumption that individuals who exhibit high levels of right-wing authoritarianism tend to stereotype perceptions of rape and assign blame to the victim (Canto et al, 2020 , 2021 ). By simply belonging to non-binary group, its members stand in opposition to the values of right-wing authoritarianism - respect for traditional social values, and entrenched thinking about gender binarity and assigned social roles for men and women.…”
Section: Discussionmentioning
confidence: 99%
“…A TDJ afirma que as pessoas camuflam o preconceito ou a discriminação, a fim de não entrar em dissonância cognitiva com suas crenças de relacionamento ideal (Paiva & Pereira, 2021). Além disso, pessoas que endossam o pensamento convencional tendem a aceitar a violência advinda de pessoas de grupos majoritários ou vistas como figuras de autoridade (Canto et al, 2020). Nessa linha, sabe-se que àquelas que apresentam uma disposição para a dominância social tendem a recorrer a crenças ideológicas para legitimar o próprio comportamento discriminatório contra minorias sociais (Pereira & Vala, 2010).…”
Section: Discussionunclassified
“…No que tange especificamente as atitudes tradicionalistas no apoio ao abuso psicológico em mulheres, sabe-se que dão ênfase ao autoritarismo, tendem a manter a hierarquia do grupo social e isto inclui as relações de gênero e que é uma característica de sociedades patriarcais mais convencionais (Canto et al, 2020). Ademais, reforça-se que no presente estudo foi considerado o autoritarismo, em sua vertente mais tradicionalista, que é caracterizado pelo etnocentrismo.…”
Section: Discussionunclassified
“…Many researchers have highlighted sexism as a dynamic risk factor that explains the main element of SVAW: the control or dominance of men over women (Bosch-Fiol & Ferrer-Perez, 2019; Çalıkoglu et al, 2018; Canto et al, 2020; Guerrero-Molina et al, 2020; Mann et al, 2010; Tharp et al, 2013). The literature has demonstrated that the relationship between hostile sexism and various manifestations of SVAW includes the justification of episodes of sexual assault (Hill & Marshall, 2018) and the tendency of men to commit rape (Abrams et al, 2003; Masser et al, 2006).…”
Section: Introductionmentioning
confidence: 99%